MENINGKATKAN KARAKTER RELIGIUS SISWA MELALUI KEGIATAN MEMBACA ASMAUL HUSNA di MTs N 11 AGAM - Tiara Mustika; Isnando Tamrin; Rosi Marlina (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The purpose of this research is to find out how far teachers at school have gone in improving students' religious character through Asmaul Husna activities at MTs N 11 Agam. This type of research uses a qualitative descriptive method. The data source can be done by interviewing several teachers and students at the MTs N 11 Agam school. The results of the research obtained are the increasing discipline, good habits and polite attitudes of students at MTs N 11 Agam. The activities have been arranged in such a way and have been structured as well as possible to make the students of MTs N 11 Agam into children who have good character and good manners and noble character, therefore an Asmaul reading activity was held. Husna every Wednesday morning to always increase students' religious values. Apart from that, this activity was held to make the students of MTs N 11 Agam into children who can respect other people and uphold religious values.